Peranan Kompetensi SDM Terhadap Peningkatan Kinerja Karyawan - Anis Anshari Masud; Andi Putri Tenriyola; Ades Asike (Amsir Management Journal, 2022)
This study describes the role of human resource competence in improving employee performance. The human resources needed by companies today are HR competencies that have the skills to adapt to new environments such as the adoption of new technologies. The role of HR competencies today requires task skills and skill transfer skills as basic characteristics (underlying characteristics) that are deep and inherent in a person that can be used to predict various specific work situations, such as technological advances in today's digital era. This study uses a qualitative research method which is carried out on the process of understanding based on facts in a social phenomenon and human problem, and presented in an analytical and descriptive manner and collected systematically. This research uses a case study approach. The results of this study indicate that preparing human resource competencies today is an easy thing. There are challenges that hinder the success or failure of the efforts undertaken. There are several challenges that must be resolved, such as the education level of employees is still low, employees who do not have the competence to develop themselves, there are still some employees who do not understand the application of technology in the work environment, and the lack of consistency in training and development that PT Mpingchips does for each of its employees. Employee education and training contribute to increasing productivity, effectiveness and efficiency of the organization. Education and training for employees at PT Mpingchips must be provided regularly so that each employee's competence is maintained to improve organizational performance